PERCEPTION OF FOREIGN WORKERS IN INDONESIAN ONLINE MEDIA COVERAGE: A DISCOURSE HISTORICAL APPROACH ANALYSIS - Heryani Heryani; Sultan Sultan; Jufri Jufri; Mantasiah R (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2025)
Media discourse plays an important role in shaping public perception and influencing the way an issue is understood, including the issue of employment and labor migration. The Discourse-Historical Approach (DHA), a method of Critical Discourse Analysis, allows the relationship between texts, socio-political contexts, and policy history to be analyzed thoroughly so that the representation strategies used by the media can be revealed systematically. This study uses DHA to examine how Indonesia's national media represents Foreign Workers and how this representation has the potential to affect public perception. The research data consisted of 30 news articles published on six national online media portals (kumparan.com, mediaindonesia.com, kompas.com, detik.com, news.republika.com, and cnnindonesia.com) between 2018 and 2025. The analysis was carried out by identifying five main discourse strategies–nomination, prediction, argumentation, perspective, and intensification–to map the construction of the image of foreign workers in the news. The results of the study show that the media presents an ambivalent representation, where foreign workers are positioned as a threat to local employment opportunities and are associated with the issue of licensing maladministration, but are also presented as agents of knowledge transfer and of national development. These findings show that media framing is not neutral and is loaded with ideological interests that can strengthen both resistance and public acceptance of labor policies. This research contributes theoretically by enriching the study of Critical Discourse Analysis in Indonesia and emphasizing the relevance of DHA in understanding the relationship between media discourse and the formation of public opinion. Practically, the results of this research can be an input for the media to produce more balanced news and for policymakers to formulate public communication that is inclusive and sensitive to public perception.